Pseudomonas aeruginosa as a culprit of cervical necrotizing fasciitis: A case report. (October 2022) - Chaurasiya, Prem Shankar; Gurung, Shekhar; Karki, Saurab; Timilsina, Bibek; Shah, Ravikant; Neupane, Sandesh
Abstract: Introduction and importance: Necrotizing fasciitis is usually a polymicrobial infection and odontogenic source is usually the foci for infection in the neck region. Cervical necrotizing fasciitis due to Pseudomonas is a rare and potentially fatal complication in diabetic patients. The study highlights the importance of early intervention to improve the outcome of the patient. Case presentation: We report a case of a 48-year female who presented with neck pain for 10 days. On further investigations, she had diabetic ketoacidosis, and a culture of the wound showed Pseudomonas. With appropriate antibiotics and surgical intervention, her condition gradually improved. Clinical discussion: Necrotizing fasciitis in the neck region with Pseudomonas without odontogenic infections is a rare occurrence. Early medical and surgical intervention leads to a better outcome. The location of the infection and its extensions can affect the prognosis. Conclusion: Physicians should be aware of cervical necrotizing fasciitis as a complication in diabetic ketoacidosis and install early treatment to improve survivability and the outcome. Highlights: The hallmark of necrotizing fasciitis is the extensive necrosis of subcutaneous tissue and underlying fascia. Cervical necrotizing fasciitis without contiguous spread is a rare occurrence. Early surgical intervention can lead to better outcome of the patient.